Finite time trajectory tracking control of underwater salvage robot under full-state constraints - Xue Bai; Yan Zhang; Wenyi Tan; Yang Liu; Baihui Jiang; Jiawei Wang (International Journal of Naval Architecture and Ocean Engineering)
Aiming at the problem that the trajectory tracking of underwater salvage robots is subject to model uncertainty and complex unknown interference when working in the marine environment, a finite time trajectory tracking control scheme based on command filtering and full-state constraint is proposed. The scheme uses the super-twisting algorithm to design the observer to accurately estimate the composite disturbance composed of model uncertainty and unknown complex time-varying disturbance in the system. Secondly, the finite-time command filter based on the first-order Levant differentiator is introduced to solve the problem of ”differential explosion” in deriving the virtual control law concerning time. The barrier Lyapunov function, backstepping control method, and finite-time control theory are combined to achieve finite time full-state constraints. Then, the control scheme is verified by Lyapunov stability, which can make the position error and velocity error of the system converge to the stable region in a finite time.